Factor and Influential Variables Affecting Maintenance Cost of Urban Rail Rolling Stock - Mohamad Idris, Mohd Firdaus; Saad, Nor Hayati; Yahaya, Mohamad Irwan; Wan Mohamed, Wan Mazlina; Shuib, Adibah; Mohamed Amin, Ahmad Nizam (International Journal of Integrated Engineering, 2023)
It is a known fact that the cost of maintaining rolling stock is huge due to its higher acquisition cost and maintenance activity. This research paper aims to analyse, evaluate, and rank the influential variables contributing towards rolling stock maintenance cost. A quantitative approach was adopted for data collection and factual data from Malaysia's rolling stock practitioners was collected using a survey. The research first identified the influential variables associated with rolling stock maintenance cost through literature review. A questionnaire survey was conducted among five Trains Operating Companies in Malaysia. These were performed using importance index to accomplish ranking analysis. The research has discovered five groups of predictor factors that affect rolling stock maintenance cost and 14 influential variables to execute the maintenance activity. This study has highlighted the possibility of future major studies in cost structure implied by group of predictors to predictive cost model for rolling stock maintenance.